(untitled) (Research, Society and Development, 2024)
The objective of the present study is to elucidate the incidence and series of diseases of the oral cavity, related to neoplasms, among residents of the Municipality of Joinville through epidemiological research of a qualitative and quantitative nature. The profile of patients living in the city of Joinville in the state of Santa Catarina treated for pathologies of the oral cavity mucosa was analyzed through the analysis of histopathological exams submitted to a laboratory in the city. Factors such as lifestyle, age and sex of those affected are involved, data obtained through reports from the laboratory system. In this study, 1,164 exams were processed from 2013 to 2023, using keywords with the search system, it was found that 655 samples were from women and 509 from men. The results demonstrated 185 different histological variants. Of these, there were 131 non-malignant variants, of which 277 results suggested fibroma. Of the malignant variants, which were 24 variants, 86 results showed carcinomas, with this lesion being predominant among those considered and synonymous with “malignant”. Of the potentially malignant variants, which were 30 variants, there were 138 tests in total. It is hoped that the data will help professionals in the field so that prevention and diagnostic strategies can be established regarding pathologies of the oral cavity of the inhabitants of Joinville.